Variation in Thyroid-Stimulating Hormone and Cognitive Disorders in Unmedicated Middle-Aged Patients with Major Depressive Disorder: A Proton Magnetic Resonance Spectroscopy Study. (5th September 2022) - Zhao, Hui; Lai, Shunkai; Zhong, Shuming; Zhang, Yiliang; Yang, Hui; Jia, Yanbin
Abstract : Background . Middle-aged (45-59 years old) patients with major depressive disorder (MDD) have a predilection for dementia and cognitive disorders (CDs); however, the characteristics and mechanisms of CDs in these patients remain unclear. There are also known connections between thyroid-stimulating hormone (TSH), brain biochemical metabolism, and cognitive function (CF); however, there is scanty of information about these connections in middle-aged MDD patients. Methods . Cognitive assessment was performed on 30 first-episode, untreated middle-aged patients with MDD and 30 well-matched healthy controls (HCs) using the MATRICS Consensus Cognitive Battery (MCCB). N-acetyl aspartate (NAA)/creatine (Cr) and choline (Cho)/Cr ratios in the prefrontal cortex (PFC) and cerebellum were also obtained via proton magnetic resonance spectroscopy ( 1 H-MRS), and the TSH level was measured by chemiluminescence analysis. Results . MDD patients presented significantly lower processing speed, working memory, verbal learning, reasoning problem-solving, visual learning, and composite cognition scores than controls, with a statistically lower NAA/Cr ratio in the right cerebellum. Age was positively related to reasoning problem-solving in the MDD group (r = 0.6249, p = 0.0220 ). Education also showed a positive association with visual learning, social cognition, and composite cognition. The 24-item Hamilton Depression Rating Scale (HDRS-24) score was negatively related to all domains of CF. TSH levels were markedly decreased in the MDD group, and a positive connection was determined between the NAA/Cr ratio in the right PFC and the TSH level. Conclusions . Middle-aged MDD patients have multidimensional CDs. There are changes in PFC and cerebellar biochemical metabolism in middle-aged patients with MDD, which may be related to CDs or altered TSH levels.